A peptide interaction in the major groove of RNA resembles protein interactions in the minor groove of DNA. - Chen, L (1995)
A 17-amino acid arginine-rich peptide from the bovine immunodeficiency virus Tat protein has been shown to bind with high affinity and specificity to bovine immunodeficiency virus transactivation response element (TAR) RNA, making contacts in the RNA major groove near a bulge. We show that, as in other peptide-RNA complexes, arginine and threonine side chains make important contributions to binding but, unexpectedly, that one isoleucine and three glycine residues also are critical. The isoleucine side chain may intercalate into a hydrophobic pocket in the RNA. Glycine residues may allow the peptide to bind deeply within the RNA major groove and may help determine the conformation of the peptide. Similar features have been observed in protein-DNA and drug-DNA complexes in the DNA minor groove, including hydrophobic interactions and binding deep within the groove, suggesting that the major groove of RNA and minor groove of DNA may share some common recognition features.